Temperature behavior of Ce3+ emission in (Lu,Y)2SiO5 single crystals excited by vacuum ultraviolet synchrotron light - Pankratova, Viktorija; Chernenko, K.; Popov, Anatoli I.; Pankratovs, Vladimirs (Elsevier B.V., 2024)
Cerium doped (Lu,Y)2SiO5 (or LYSO) single crystals have been studied by means of luminescence excitation spectroscopy in the temperature range from 7 up to 300 K. Vacuum ultraviolet excitations in 4.5–8 eV energy range from synchrotron radiation of 1.5 GeV storage ring of MAX IV synchrotron facility. It is shown that both type of Ce3+ emission centers (seven and six coordinated centers) are excited under any excitation energy used. It was concluded that the same energy transfer processes from host lattice to impurity ions are involved independently on coordination of Ce3+. It is also demonstrated that excitonic mechanism of energy transfer is dominant under chosen excitation and intrinsic and bound excitons are included in excitation of Ce3+ luminescence in LYSO. © 2024 The Author(s) --//-- This is an open-access article V. Pankratova, K. Chernenko, A.I. Popov, V. Pankratov, Temperature behavior of Ce3+ emission in (Lu,Y)2SiO5 single crystals excited by vacuum ultraviolet synchrotron light, Optical Materials: X, Volume 22, 2024, 100322, ISSN 2590-1478, https://doi.org/10.1016/j.omx.2024.100322.
The authors declare the following financial interests/personal relationships which may be considered as potential competing interests:Vladimir Pankratov reports financial support was provided by University of Latvia Institute of Solid State Physics. Viktorija Pankratova reports financial support was provided by University of Latvia Institute of Solid State Physics. Anatoli I Popov reports financial support was provided by University of Latvia Institute of Solid State Physics. Kirill Chernenko reports financial support was provided by MAX IV Laboratory. If there are other authors, they declare that they have no known competing financial interests or personal relationships that could have appeared to influence the work reported in this paper.The work of Vladimir Pankratov is supported by the LZP grant (2022/1-0611). Viktorija Pankratova and A.I.P. acknowledge the State Research Program VPP-IZM-CERN-2022/1-0001. The Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2. We acknowledge MAX IV Laboratory for time on FinEstBeAMS Beamline under Proposal 20211074. Research conducted at MAX IV, a Swedish national user facility, is supported by the Swedish Research council under contract 2018-07152, the Swedish Governmental Agency for Innovation Systems under contract 2018-04969, and Formas under contract 2019-02496. We thank our colleagues from the California Institute of Technology (Caltech), particularly Adi Bornheim, for providing us with a sample of the crystal material studied.
Keywords: Research Subject Categories::NATURAL SCIENCES; (Lu,Y)2SiO5:Ce3+; LSO; LYSO; Scintillators; Synchrotron radiation; VUV spectroscopy; YSO